The Effects of Corporate Social Responsibility on Brand Performance: The Mediating Effect of Industrial Brand Equity and Corporate Reputation - Lai, Chi-Shiun (Journal of business ethics, 2010)
In this article, the researchers explore the following question. Can corporate social responsibility (CSR) and the corporate reputation of a firm lead to its brand equity in business-to-business (B2B) markets? This study discusses CSR from customers’ viewpoints by taking the sample of industrial purchasers from Taiwan small-medium enterprises. The aims of this study are to investigate: first, the effects of CSR and corporate reputation on industrial brand equity; second, the effects of CSR, corporate reputation, and brand equity on brand performance; and third, the mediating effects of corporate reputation and industrial brand equity on the relationship between CSR and brand performance. Empirical results support the study’s hypotheses and indicate that CSR and corporate reputation have positive effects on industrial brand equity and brand performance. In addition, corporate reputation and industrial brand equity partially mediate the relationship between CSR and brand performance.